DAMPAK DEMOGRAFI DAN STATUS KEPEGAWAIAN TERHADAP KOMITMEN KARIER PADA PROFESI GURU - Anindra Guspa; Zulmi Yusra (Universitas Negeri Padang, 2023)
Study career commitment or Commitment career been a long time object study in psychology industry and Organization . Commitment career is very important researched remember every individual who works and falls in A profession certain will have commitment career the including profession Teacher. The teaching profession is mandated as A professional profession . _ Professionality a Master is shown with exists Certification Teacher Profession and Teacher Professional Program established by the government . As a individual a teacher is certainly in demand For commitment with career them , however There is a number of sticky thing _ like factor demographics , and employment status to be impact as well asÂ influence Commitment Career a teacher. Therefore the author submits study predictive about commitment career teaching profession with predictor demographics and employment status . This research is study base and is advanced from study previously ie profile commitment career teacher profession . Study This is study quantitative with use triple ANOVA data analysis track with amount subject 118 (N=118) who was a teacher already own certification profession . Research results This find that gender and employment status in a manner together in a manner significant impact to commitment career a teacher. If all variables ( demographics and employment status ) stand Alone so in a manner significant No impact to commitment career .